Estimation of Household’s Meat Consumption Elasticities in Khyber Pakhtunkhwa, Pakistan - Muhammad Jibran; Shahid Ali; Irfan Ullah; Nargis Bibi; Fida Muhammad Khan (Indus Journal of Social Sciences, 2025)
The study investigated meat consumption elasticities in Peshawar district of Khyber Pakhtunkhwa. Data was collected from 120 households from Hayatabad and City in Peshawar District, randomly selected through a well-structured interview schedule. Working-Lesser model was employed for estimation of own-price, cross-price and expenditure elasticities. The average price of beef, mutton, poultry and fish was 1150, 1950, 869 and 860, respectively. The Working-Lesser model empirical findings for beef, poultry, and fish show that budget shares are inversely related with total meat expenditure, whereas mutton expenditure share is directly related with total meat expenditure. Mutton is income elastic while beef, poultry and fish are income inelastic. All meat types have elastic own prices, and cross prices reveals that majority of items are substitutes for one another while fish is complement for poultry. Poultry consumption is directly affected by the household size. Consequently, while formulating national policies, these findings need to be considered.